Multiscale Simulations on the Catalytic Plasticity of CYP76AH1 - Qiu, Yufan; Diao, Hongjuan; Zheng, Ying; Wu, Ruibo (Frontiers in Chemistry, 2021)
The catalytic promiscuity and fidelity of Cytochrome P450 enzymes are widely existed in the skeleton modification of terpenoids natural products, and attract many attentions. CYP76AH1 participates critical modification reactions in the biosynthetic pathway of tanshinones (a famous pharmaceutical norditerpenoid). In this work, classical molecular dynamic (MD) simulations, metadynamics and DFT calculations were performed to investigate the protein conformational dynamics, ligand binding poses and catalytic reaction mechanism in wide type and mutant CYP76AH1. Our findings not only reveal the plausible enzymatic machinery of leading various products by mutant CYP76AH1 while single product in wild type, but also provide valuable guidance for rational protein engineering of CYP76 family.